The Effectiveness of Blended Learning Using Moodle on Student Independence and Learning Outcomes - Sari, Ressa Novinta; Amalia, Andin Vita (Universitas Negeri Semarang, 2021)
This study aimed to determine the blended learning model's effectiveness using Moodle on the human respiratory system learning material's independence and student learning outcomes. This research type is a quasi-experimental type nonequivalent control group design with the sampling technique using purposive sampling. The observation results showed that the experimental class learning independence average was better than the control class. This is in line with the results of the student learning independence questionnaire. The average value of cognitive learning outcomes through the t-test shows a significant difference between the experimental and control classes. The analysis of the improvement in students' cognitive learning outcomes showed that the experimental class was more significant than the control class in the moderate category. Based on this, it can be concluded that blended learning using Moodle is useful for student independence and learning outcomes.